Análise experimental do escoamento líquido-sólido-gás no padrão golfadas em dutos horizontal - Marcos Rosas, Luis Miguel (2016)
Multiphase flows appear during a large number of industrial operations, as in the case of oil and gas offshore production operations, where solid particles, such as sand and hydrates may occasionally be present in the flow, starting the solid-liquid-gas flow. Slug flow in ducts is a frequently observed flow regime in oil and gas transportation lines. The onset of this kind of flow is due to instabilities generated by irregular pipe topography. Understanding the hydrodynamics of the slug flow is significant in the design of crude oil production lines as well as in the project of equipment involved in oil and gas operations. The present work experimentally characterizes the gas-liquid-solid three-phase flows in a horizontal pipe. The objective here is to determine the role played by solid particles (similar to hydrates) on the characteristic parameters of slug flows, namely the bubble front velocity, unit cell frequency and bubble and liquid slug lengths. Experimental tests with solid particles (whose specific mass are similar to those of the hydrate particles) dispersed in the liquid were carried out. The test section comprised a 26 mm ID, 9 m long transparent acrylic pipe. The flow structures were monitored and measured by means of resistive sensors and a high-speed camera. Several pairs of gas and liquid superficial velocities, for which the slug flow regime was observed, at different solid particle concentration were investigated during the tests. Synthetic standard 0.5 mm diameter polyethylene particles with 938 kg/m3 density constituted the solid phase. Water and compressed air were used as the liquid and gas phase, respectively. The signals captured during the tests were processed and presented in terms of a probability density function (PDF) and averaged values. The experiments and their results are discussed and compared to the two-phase gas-liquid flows at similar conditions. It was observed that solid particles influence positively the bubble front velocity and frequency, and influence negatively the piston and bubble lengths.